The environmental effects of poverty programs and the poverty effects of environmental programs: The missing RCTs. - Alpízar, Francisco (2019)
For decades, government agencies and nongovernmental organizations have invested in programs aimed at alleviating poverty and those aimed at protecting the environment. Whether these investments mutually reinforce each other or act in opposition has been widely debated by scholars. Studies that have tried to resolve this debate suffer from a variety of shortcomings, including the challenge of inferring causal relationships from non-experimental data. To help address some of these shortcomings, randomized controlled trials (RCTs) can play an important role. When done well, RCTs permit credible causal inferences and can be designed to directly test competing assumptions about how the world works. Yet few RCTs of poverty programs examine their effects on the environment. Worse, we know of no RCTs reporting the poverty effects of environmental interventions, which may be unsurprising given that environmental scholars rarely use RCTs. The lack of RCTs that can shed light on the relationships between actions to alleviate poverty and actions to reverse global environmental change is an obstacle to advancing the science and practice of sustainability. If scholars of poverty include environmental outcomes in their RCTs, and if environmental scholars use RCTs to study the poverty effects of environmental programs, the longrunning debates about the dual challenges of alleviating poverty and protecting the environment could be resolved...